Narratives of fungal-based materials for a new bioeconomy era. - Delvendahl, Nora; Dienel, Hans-Liudger; Meyer, Vera; Langen, Nina; Zimmermann, Jennifer; Schlecht, Martin (Innovation: The European Journal of Social Sciences, 2023)
Newly developed fungal-based materials have promising potential with regard to mitigating greenhouse gas emissions and enabling a shift towards a more circular economy. However, an important step towards their success in the bioeconomy is consumers' acceptance and sustainable consumption of these materials. Highlighting the power of narratives, this paper looks at the symbolic nature of fungi and discusses how common perceptions can be reshaped through narrative structures. We first identify common expectations, hopes and fears of fungi and then focus on how potentially negative beliefs or fears regarding fungal-based materials can be transformed through disseminating and reframing scientific information in a narrative structure. Specifically, we discuss characteristics of a story that can induce changes in attitudes and behaviours among consumers to induce sustainable consumer choices. To adjust and promote these sustainable narratives within the society, we suggest innovative science communication and especially citizen participation formats as adequate tools.